A Lower Palaeozoic 'onychophoran' reinterpreted as a pelmatozoan (stalked echinoderm) column - Rhebergen, Freek; Donovan, Stephen (Atlantic Geology, 1994)
Onychophorans are rare fossils, but are currently the subject of renewed research activity. However, not all 'onychophorans' have been correctly identified. The specimen described herein is preserved as a natural mould in an Upper Ordovician cobble from a Quaternary glacial deposit. The 'legs' are actually elongate tubercles, arranged in irregular circlets and showing calcite cleavage; the annulations of the body are irregularly spaced. The specimen is reinterpreted as a pelmatozoan, probably crinoid, pluricolumnal.